POLITIK IDENTITAS MINANG DAN MULTIKULTURALISME DALAM FILM ”TENGGELAMNYA KAPAL VAN DER WIJCK” - Kustiawan Tufail; Aditya Wahyu Saputra; Dyas Puzi Rahmadina; Kharisma Putri Balqis; M. Nursyawal; Nur Thasya Mustiqa Putri; Syaihidina Hefir; Wiky Dwifa Abial; Zhahara Dwi Amanda; Abial, Wiky (STISIP Widyapuri Mandiri Sukabumi, 2024)
This scientific paper aims to find out the politics of identity and multiculturalism contained in the film ‘Tenggelamnya Kapal Van Der Wijck’. This research analyses identity politics and multiculturalism in the film ‘Tenggelamnya Kapal Van Der Wijck’. Through in-depth analysis, it is found that social inequality in Minangkabau society is an important factor influencing the dynamics of this film. Identity politics emerges through the concepts of treasure and custom that dominate social interactions, where power and social status become the main determinants in decision-making, especially in relationships between characters. The film also reflects Bugis cultural values, such as loyalty and honour, which become the foundation for the main character in facing life's challenges. In addition, multiculturalism in this film can be seen from the representation of Minangkabau culture, acculturation with Western culture, and the prominent social differences between the main character who comes from Makassar and the Minangkabau community. In conclusion, this film confirms that identity politics and multiculturalism play a significant role in shaping the narrative and dynamics between characters, and reflects the cultural complexity that exists in Indonesian society.